Giant UV photoresponse of a GaN nanowire photodetector through effective Pt nanoparticle coupling - Zhang, Xinglai; Liu, Qingyun; Liu, Baodan; Yang, Wenjin; Li, Jing; Niu, Pingjuan; Jiang, Xin (Journal of materials chemistry. C, Materials for optical and electronic devices, 2017)
High performance ultraviolet (UV) photodetectors based on semiconducting nanowires are expected to have extensive applications in UV-ray detection, optical communication and environmental monitoring. In this work, GaN nanowire photodetectors have been fabricated and giant UV photoresponse has been achieved with Pt nanoparticle (NP) modification. The peak responsivity and external quantum efficiency (EQE) of the GaN nanowire UV photodetector were increased from 773 to 6.39 × 10 4 A W −1 and from 2.71 × 10 5 % to 2.24 × 10 7 %, respectively, and the response time and sensitivity were improved greatly after Pt NP decoration on the GaN nanowire surface. Moreover, the Pt–GaN nanowire photodetector still presents its spectrum selectivity in the UV region. Our results reveal that Pt nanoparticles play a key role in enhancing the photodetection performance of the nanodevice due to the strong absorption and scattering of incident light induced by localized surface plasmon resonance (LSPR) and the improvement of interfacial charge separation owing to the special device configuration. These findings offer an efficient avenue toward the performance enhancement of GaN nanowire and related optoelectronic devices or systems.